Microbial Shifts and Shorter Time to Bowel Resection Surgery Associated with C. difficile in Pediatric Crohn's Disease. Issue 8 (14th November 2019) - Hellmann, Jennifer; Andersen, Heidi; Fei, Lin; Linn, Aaron; Bezold, Ramona; Lake, Kathleen; Jackson, Kimberly; Meyer, Danielle; Dirksing, Kelsie; Bonkowski, Erin; Ollberding, Nicholas J; Haslam, David B; et al.
Abstract: Background: Clostridioides difficile infection and colonization are common in pediatric Crohn's disease (CD). Our aims were to test the relationship between C. difficile positivity and bowel resection surgery and to characterize microbial shifts associated with C. difficile carriage and surgery. Methods: A retrospective single-center study of 75 pediatric CD patients tested for association between C. difficile carriage and bowel resection surgery. A prospective single-center study of 70 CD patients utilized C. difficile testing and shotgun metagenomic sequencing of fecal samples to define microbiota variation stratified by C. difficile carriage or history of surgery. Results: The rate of bowel resection surgery increased from 21% in those without C. difficile to 67% in those with ( P = 0.003). From a Kaplan-Meier survival model, the hazard ratio for time to first surgery was 4.4 (95% CI, 1.2–16.2; P = 0.00) in patients with positive C. difficile testing in the first year after diagnosis. Multivariable logistic regression analysis confirmed this association (odds ratio 16.2; 95% CI, 2.2–120; P = 0.006). Larger differences in microbial abundance and metabolic pathways were observed in patients with prior surgery than in those with C. difficile carriage. Depletion of Alistipes and Ruminococcus species and reduction in methionine biosynthesis were noted in patients with both C. difficile carriage and past surgery. Conclusions: A positive C. difficile test during the first year after diagnosis is associated with decreased time to first bowel resection surgery in pediatric Crohn's disease. Depletion of beneficial commensals and methionine biosynthesis in patients with C. difficile carriage may contribute to increased risk for surgery. Abstract : In the first year after diagnosis, C. difficile is associated with shorter time to first surgery in pediatric Crohn's disease. Reduction in beneficial commensals and methionine biosynthesis in those with C. difficile may contribute to this increased risk.